Weed management options for improving yield and economics of pigeonpea in Odisha - Panda, P.K.; Kar, A.; Panigrahi, R.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif season of 2014-15 and 2015-16 at the Centre forPulses Research , OUAT, Berhampur to identify suitable integrated weed management technologyand optimize proper herbicide combination for pigeonpea. Nine treatments viz. T1: Weedy check,T2: Pendimethalin 750 g/ha + Hand weeding/ inter culture at 50 DAS, T3: EPOE Imazethapyr 75g/ha at 15 DAS + HW/IC at 50 DAS, T4: EPOE Imazethapyr 75 g/ha at 10 DAS + Quizalofop ethyl50 g/ha at 15 DAS, T5: Tank mix application of Imazethapyr 75 g/ha + Quizalofop ethyl 50 g/haat 15 DAS, T6: T4 + HW/IC at 50 DAS, T7: T5 + HW/IC at 50 DAS, T8: Pendimethalin 750 g/ha +EPOE Imazethapyr 60 g /ha at 15 DAE of weeds and T9: Weed free check , were tested inRandomised Block Design. The growth and yield attributes of pigeonpea were significantly affectedby weed management practices. Among the treatments, the lowest weed density and weed drymatter (WDM) along with the highest weed control efficiency (WCE) at 30, 50 & 70 DAS wererecorded in T7 , which was very close to the weed free check. Yield attributes like, number ofprimary fruiting branches/plant, number of pods/plant, number of seeds/pod were maximum inT7 and ultimately the highest grain yield (1278 kg/ha) was recorded in T7( Tankmix of imazethapyr75 g/ha & quizalofop ethyl 50 g/ha +HW). However, the highest B:C ratio (3.51) was registeredwith T8 , despite the highest net return (Rs. 37127/ha) obtained from T7.